2009
DOI: 10.1101/gad.547309
|View full text |Cite
|
Sign up to set email alerts
|

PiggyMac, a domesticated piggyBac transposase involved in programmed genome rearrangements in the ciliate Paramecium tetraurelia

Abstract: Programmed genome rearrangements drive functional gene assembly in ciliates during the development of the somatic macronucleus. The elimination of germline sequences is directed by noncoding RNAs and is initiated by DNA double-strand breaks, but the enzymes responsible for DNA cleavage have not been identified. We show here that PiggyMac (Pgm), a domesticated piggyBac transposase, is required for these rearrangements in Paramecium tetraurelia. A GFP-Pgm fusion localizes in developing macronuclei, where rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
331
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(344 citation statements)
references
References 38 publications
8
331
1
4
Order By: Relevance
“…This new report from Baudry et al (2009) shows that Paramecium uses what was once a transposase from a piggyBac element to reorganize its somatic genome. When this putative endogenous transposase was fused to green fluorescent protein, it localized to developing MACs where DNA elimination occurs, leading Baudry et al (2009) to call this gene PiggyMac (PGM). To further assess the possibility that Pgm participated in DNA elimination, the group knocked down PGM levels by feeding Paramecium bacterial cells expressing PGM-specific dsRNA prior to inducing autogamy.…”
Section: Piggymac: the Domestication Of A Transposasementioning
confidence: 99%
See 4 more Smart Citations
“…This new report from Baudry et al (2009) shows that Paramecium uses what was once a transposase from a piggyBac element to reorganize its somatic genome. When this putative endogenous transposase was fused to green fluorescent protein, it localized to developing MACs where DNA elimination occurs, leading Baudry et al (2009) to call this gene PiggyMac (PGM). To further assess the possibility that Pgm participated in DNA elimination, the group knocked down PGM levels by feeding Paramecium bacterial cells expressing PGM-specific dsRNA prior to inducing autogamy.…”
Section: Piggymac: the Domestication Of A Transposasementioning
confidence: 99%
“…To further assess the possibility that Pgm participated in DNA elimination, the group knocked down PGM levels by feeding Paramecium bacterial cells expressing PGM-specific dsRNA prior to inducing autogamy. This treatment resulted in a 20-fold reduction in progeny production and thus revealed that the gene product has a critical function during development (Baudry et al 2009). …”
Section: Piggymac: the Domestication Of A Transposasementioning
confidence: 99%
See 3 more Smart Citations